Sidama Coffee Agronomy Program: Impact report - Abate, Gashaw T.; Regassa, Mekdim D.; Bernard, Tanguy; Minten, Bart (International Food Policy Research Institute, 2025)
Coffee is Ethiopia’s most important export crop, and it constitutes an important source of livelihood for an estimated 15 million people across the value chain, most of whom are poor smallholder farmers. While coffee production and exports generally increased over the last decade or so, several constraints are still keeping the sector from attaining its full potential. Low-yielding, aged coffee trees and poor farm management and agronomic practices are among the main constraints. Between 2019 and 2022, TechnoServe (TNS)—in collaboration with Max und Ingeburg Herz Stiftung/HereWeGrow (HWG)— implemented a 25-month coffee agronomy training program in the Sidama region of Ethiopia that comprised a package of interventions to address these constraints and increase smallholders’ coffee productivity and income. In particular, the program covered five woredas/districts (Aleta Chuko, Dale, Bona Zuria, Hawela, Shebedino) and reached 47,759 farm households in two cohorts (2019 and 2020).